RELEVANSI KOMPETENSI LULUSAN SMK KOMPETENSI KEAHLIAN BISNIS KONSTRUKSI DAN PROPERTI DENGAN KOMPETENSI YANG DIPERLUKAN DI DUNIA KERJA - Rananda Ahmad Tauhid; Dedy Suryadi; Parmono Parmono (Universitas Pendidikan Indonesia (UPI), 2022)
This study aims to determine the competence of graduates at SMKN 1 Cibinong Construction and Property Business Skills Program, determine the competencies needed in the world of work according to SKKNI and determine the relevance of graduates of SMKN 1 Cibinong Construction and Property Business Expertise Competencies with the world of work. This study uses a descriptive research method with a qualitative approach. The instrument used in this research is a documentation study. The documents used are the syllabus of SMKN 1 Cibinong, competence in construction and property business skills and SKKNI number 193 of 2021 for the position of implementing the building construction field. Based on data analysis, it was found that the description of the competencies possessed by graduates is 82 points and the competencies needed in the world of work according to the SKKNI are 7 points, while the competencies of graduates of SMKN 1 Cibinong, the competencies of construction and property business skills, are not relevant to the competencies needed in the world of work.